1971
DOI: 10.1111/j.1532-5415.1971.tb01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Confusional States in Relation to Vitamin Deficiencies in the Elderly

Abstract: The author uses case abstracts to illustrate deficiencies of thiamine! vltamln-B complex and vitamin C associated with confusional states in the elderly. The biochemical indicators were chiefly the pyruvate metabolism test and the level of ascorbic acid in the leukocyte layer ("buffy coat") of the blood. The confusional states usually disappeared or improved with appropriate vitamin therapy.Nutritional deficiencies are being recognized with increasing frequency in the practice of geriatric medicine. Among elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Nonetheless, the overall trend from the studies included in this systematic review indicates that vitamin C deficiency is associated with an increase in depression [21,24,25] and cognitive impairment [27][28][29]. Scurvyi.e., vitamin C deficiency with physical manifestationsis also associated with depression [22,23] and confusion [26]. Given the paucity of research in this area to date, one fruitful avenue for future research would be specifically investigating whether vitamin C deficiency is linked to other psychiatric diagnoses, including psychosis and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, the overall trend from the studies included in this systematic review indicates that vitamin C deficiency is associated with an increase in depression [21,24,25] and cognitive impairment [27][28][29]. Scurvyi.e., vitamin C deficiency with physical manifestationsis also associated with depression [22,23] and confusion [26]. Given the paucity of research in this area to date, one fruitful avenue for future research would be specifically investigating whether vitamin C deficiency is linked to other psychiatric diagnoses, including psychosis and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In this present systematic review, the included studies in this review employed a number of different measurement techniques for vitamin C, including blood levels, leucocyte levels and a vitamin C saturation test. For the included case series of clinical vitamin C deficiency, two older studies published in 1968 and 1971 primarily utilised leucocyte ascorbic acid level [22,26]. Walker [22] measured vitamin C in milligram per 100 mg of white blood cells, while Mitra [26] measured vitamin C in milligram per 100 g of white blood cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This deficiency may occur because of a low dietary intake or because of malabsorption. Mitra (31) concluded that B 12 deficiency, along with folic‐acid deficiency, may be a cause of dementia and confusional states in the elderly. Elsborg et al (32) investigated serum B 12 levels in 273 geriatric patients and found a low level in one‐third of them.…”
Section: Drugs Frequently Used By the Elderly Which Can Affect The Abmentioning
confidence: 99%